Two-Way Approach in The Concept of Improving Digital Selling for Typical Bugis-Makassar Female Entrepreneurs - Nurlinda, Nurlinda; Alam, Andi Rifqah Purnama; Irawan, Indra (SENTRALISASI, 2025)
Women in the beauty sector play a role in developing the business world and using the digital economy. In South Sulawesi, female entrepreneurs utilize the uniqueness of the Bugis-Makassar tribe to produce skincare products known as Badda' Lotong. Through a two-way approach and mixed-method research, the objectives of this study are to (1) Analyze the effect of live streaming on impulsive buying and digital selling, (2) Analyze women's impulsive buying behavior, (3) Analyze the increase in digital selling of the Badda' Lotong business. The study results show that live streaming can encourage impulsive customer behavior so that they decide to make product purchases. The use of technology through online marketing on social media and sales in the marketplace has been proven to increase seller income.